Impact of hybrid procedure on pulmonary arterial dimensions and right ventricular load after biventricular repair - Uhl, Sebastian; Grieshaber, Philippe; Arnold, Raoul; Loukanov, Tsvetomir; Gorenflo, Matthias (Journal of cardiothoracic surgery, 2023)
Background: Hybrid procedure with ductal stenting and bilateral pulmonary banding offers a temporary approach in high-risk neonates with complex congenital heart defects aiming biventricular repair. This procedure may also have negative impact concerning post-banding pulmonary stenosis resulting in right ventricular pressure load. Methods: Between 2010 and 2021 we identified 5 patients with interrupted aortic arch and complex congenital heart defect who underwent hybrid procedure and staged biventricular repair (“hybrid-group”). Other 7 cases with interrupted aortic arch were corrected in the neonatal phase without hybrid procedure (“nonhybrid-group”). Detailed intra- and extracardiac features and surgical procedures were documented as well as pulmonary interventions during follow up. Pulmonary vessel size was assessed by diameter of left and right pulmonary artery in absolute and indexed values. RV pressure was evaluated invasively via catheterization. Results: Survival in cases with hybrid procedure and staged biventricular repair was 91% for a follow-up time of 40.7 months (95% CI 26–55 months) and 100% in the non-hybrid-group. Postoperative results concerning left ventricular function showed normal LV dimensions and systolic function without relevant stenosis on distal aortic arch. Hybrid procedure was associated with impaired local pulmonary arterial diameter after debanding resulting in increased right ventricular pressure and need for interventions (number intervention per patient: hybrid group 1.7 ± 0.95, non-hybrid group 0.17 ± 0.41; P 0.003). Conclusions: Hybrid procedure in high-risk cases with interrupted aortic arch and staged biventricular repair shows good postoperative results with low perioperative mortality and normal left ventricular function. Due to potential risk of relevant pulmonary stenosis and right ventricular pressure load, follow up examinations must not only focus on left but also on the right heart.
Gesehen am 14.03.2023